Comparative analysis of stress and deformation distribution in implant supported telescopic systems made of different materials - Bojović Milan; Todić Jelena; Blagojević Milan (Vojnosanitetski Pregled)
Background/Aim. In implant prosthetics, there is an increasing use of materials that, with their mechanical characteristics, can alleviate the negative consequences of implant stress. The aim of this study was to conduct a comparative analysis of stress distribution and deformation of implant-supported telescopic systems and surrounding structures made of different materials using the finite element method. Methods. The 3D finite element models were prepared using the SolidWorks program (SolidWorks 2018, Concord, MA, USA). Two models of telescopic crowns with the characteristics of polyetherether-ketone (PEEK) polymer and cobalt-chromium (Co-Cr) alloy faceted with feldspar ceramics were used. The models were loaded with an axial force of 150 N in the region of the central fossa. The analysis of stress and strain distribution was per-formed by the finite element method in the Ansys software (ANSYS Workbench 16; Ansys Inc., Pittsburg, PA, USA). Results. Implant-supported telescopic crowns made of PEEK polymer significantly reduced stress in the implant and abutment neck area compared to the conventional Co-Cr crown veneered ceramic. At the level of bone structure, both models showed a concentration of stress at the level of the cortical bone, while the trabecular bone was significantly less exposed to stress. Under the same conditions, the degree of deformation of the secondary telescopic crown was more pronounced in models with PEEK polymer characteristics. Conclusion. Owing to their mechanical characteristics, PEEK polymers can be the materials of choice in the fabrication of superstructures on implants. Given that this in vitro study was accompanied by limitations, further research is needed to confirm the superior role of PEEK material in implant prosthetics.